The Magnificent of DNA Coding - Ibrahim, Nur Aifiah Binti (Darul Yasin Al Sys, 2025)
DNA coding and labelling are for tagging the naming of a species and their functionality bodies. The blood composition and other external breeding are not forming new mutant cells to be hybrid on this planet Earth. Therefore, in Atlantis, there are many new plots and blueprints imprinted on the minds of creators. Even a navigation map and electrified compass were used to measure the coverage area of fishing and hunting for a treasury in the quest. Looking for a fish is fascinated by the mechanistic working of the gills and fins. The body movement works in a way to overcome the current, and the wave will hit the fish harshly. Instead, the fish figured it out and flipped several times without feeling tired. Every other moment, the predator will find a way to hunt for their nests without preserving their nature of living under the seawater. The sea is so vast that the predators, even the gigantic ones, have nowhere to hide.